Deceptive intensities: An exploratory strategy for overcoming early central fatigue in resistance training - Gorzi, A.; Rezapour, N.; Jabbari, S.; Youzbashi, L.; Salehi, J.; Gahreman, D.; Neto, W. K. (Physiology & Behavior, 2022)
Neuropsychological stress induced by misleading information can limit human performance, possibly by early central fatigue mechanisms. In this study, we investigated the impact caused by prescribing misleading intensities of resistance exercise on acute electroencephalogram (EEG) and electromyogram (EMG) responses and the total number of repetitions to exhaustion. Collegiate female students performed three sets of biceps curls to exhaustion. The actual intensity for all sets was set at 65% 1-Repetition Maximum (1-RM). However, participants were deceptively informed that the intensities were 60%, 65%, or 70% 1-RM. The number of repetitions to fatigue and the magnitude of EEG and EMG signals were analyzed. The number of repetitions to exhaustion was significantly lower in greater announced intensities (18.11 ± 8.44) compared to lower (29.76 ± 16.28; p = 0.017) and correctly (27.82 ± 11.01; p = 0.001) announced intensity. The correlation between frontal and motor-cortex signals was significant in lower (r = 0.72, p = 0.001) and higher (r = 0.64, p = 0.005) announced intensities. The median and mean frequencies of EMG signal and Root Mean Square (RMS) did not show any significant difference between sets, but the peak-to-peak range (PPR) of biceps EMG signals was significantly higher in lower intensity (0.145 ± 0.042) when compared with higher (0.104 ± 0.044; p = 0.028) or correctly (0.126 ± 0.048; p = 0.037) announced intensity. It seems that deceptive information regarding the mass of an object could affect the number of repetitions to exhaustion and PPR to cover muscle capacity in endurance-type strength training.